2010
DOI: 10.1063/1.3294573
|View full text |Cite
|
Sign up to set email alerts
|

The effect of viscoelasticity on the stability of a pulmonary airway liquid layer

Abstract: The lungs consist of a network of bifurcating airways that are lined with a thin liquid film. This film is a bilayer consisting of a mucus layer on top of a periciliary fluid layer. Mucus is a non-Newtonian fluid possessing viscoelastic characteristics. Surface tension induces flows within the layer, which may cause the lung's airways to close due to liquid plug formation if the liquid film is sufficiently thick. The stability of the liquid layer is also influenced by the viscoelastic nature of the liquid, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 45 publications
(43 reference statements)
4
54
0
Order By: Relevance
“…Figure 4 shows comparisons of the dimensionless histories of the maximum interfacial velocity and R min (the minimum distance between the interface and the centreline) between the lubrication theory model (Halpern, Fujioka & Grotberg 2010) and the SIM with L = 9.0, ε = 0.2 and Re = 1.0. Results shown in figure 4 demonstrate good agreement between both approaches until t = 18, and an increasing deviation occurs between them after t = 18.…”
Section: Validationmentioning
confidence: 99%
“…Figure 4 shows comparisons of the dimensionless histories of the maximum interfacial velocity and R min (the minimum distance between the interface and the centreline) between the lubrication theory model (Halpern, Fujioka & Grotberg 2010) and the SIM with L = 9.0, ε = 0.2 and Re = 1.0. Results shown in figure 4 demonstrate good agreement between both approaches until t = 18, and an increasing deviation occurs between them after t = 18.…”
Section: Validationmentioning
confidence: 99%
“…Finally, Grotberg and colleagues have developed several models to account for liquid plug formation, motion, and rupture. 98101 Although these biophysical models have significantly advanced our understanding of the fluid mechanics of airway recruitment/derecruitment, they do not directly simulate cellular deformation during reopening, and can therefore only infer potential injury mechanisms. Since the injury response of epithelial cells is clearly related to the amount of deformation, our laboratory has developed several unique and sophisticated models of cellular deformation during airway reopening that account for complex morphological, biomechanical, and fluid-structure interactions.…”
Section: Mathematical Models Of Recruitment/derecruitmentmentioning
confidence: 99%
“…The Marangoni stresses induced by uneven distribution of interfacial surfactant concentration oppose the closure ow. Halpern et al [20], using lubrication theory, showed that viscoelasticity does not strongly aect the critical lm thickness h c /a, and for h c /a < 0.119 airway closure does not occur within a breathing cycle. On the other hand, if 14% ≤ h/a ≤ 18%, increasing the Weissenberg number speeds up the growth rate when the viscoelastic uid exhibits a shear-thinning behavior.…”
Section: Introductionmentioning
confidence: 99%